Peningkatan Produktivitas UKM Cahya Interior Decoration (CID) Melalui Pemanfaatan Teknologi Mesin Pelapis High Pressure Laminated (HPL) - Hadi, Afif Abdul; Kusumawardan, Arya; Habibi, Muhammad Afnan; Mahadiraja, Fajar Abdi; Satriani, Cahya Tifandi; Octavianus, Juan Pablo; Haqiqi, Ahmad Faiz Risvan (Bahasa Indonesia, 2025)
UKM Cahya Interior Decoration (CID) in Kabupaten Madiun faces challenges in the High Pressure Laminated  lamination process on multiplex wood, which is currently performed manually. This process requires 5 minutes per m², resulting in prolonged production times and low efficiency. The community service initiative aims to design and implement an HPL laminating machine that can enhance the time efficiency of the lamination process. The developed machine integrates a spring adjustment mechanism and roll press, and is equipped with a ½ hp motor and a 1:30 gearbox, enabling the lamination process to be completed in only 0.75 minutes per m². Designed to be compact and efficient, the machine is capable of increasing the production capacity from 3 to 4 products per day. Furthermore, the machine has successfully reduced the total production time per product from 135 minutes to 101 minutes, leading to an increase in the monthly product output from 78 to 104 units. The implementation of this HPL laminating machine technology has significantly improved both efficiency and production capacity, thereby enhancing CID’s competitiveness and its ability to meet higher market demand. It is hoped that this technology can be adopted by similar industries to support the development of small manufacturing enterprises.   Abstrak UKM Cahya Interior Decoration (CID) di Kabupaten Madiun menghadapi tantangan dalam proses pelapisan HPL pada kayu multiplex yang dilakukan secara manual. Proses ini memerlukan waktu 5 menit per m², menyebabkan durasi produksi yang lama dan efisiensi yang rendah. Inisiatif pengabdian masyarakat ini bertujuan untuk merancang dan menerapkan mesin pelapis HPL yang dapat meningkatkan efisiensi waktu pelapisan. Mesin yang dikembangkan mengombinasikan elemen penyesuaian pegas (spring adjustment) dan roll press, serta dilengkapi dengan motor ½ hp dan gearbox 1:30 yang memungkinkan pelapisan selesai dalam waktu hanya 0,75 menit per m². Mesin ini dirancang dengan ukuran yang kompak dan efisien, serta mampu meningkatkan kapasitas produksi dari 3 menjadi 4 produk per hari. Selain itu, mesin ini juga berhasil mengurangi waktu total produksi per produk dari 135 menit menjadi 101 menit, yang berdampak pada peningkatan jumlah produk bulanan dari 78 menjadi 104 unit. Penerapan teknologi mesin pelapis HPL ini memberikan dampak signifikan dalam meningkatkan efisiensi dan kapasitas produksi, sehingga meningkatkan daya saing dan kemampuan CID untuk memenuhi permintaan pasar yang lebih tinggi. Teknologi ini diharapkan dapat diadopsi oleh industri sejenis guna mendukung pengembangan industri manufaktur kecil.